E-033 The smoking-thrombolysis paradox in large vessel occlusion acute ischemic stroke after endovascular therapy. (23rd July 2017) - Grossberg, J; Bouslama, M; Rebello, L; Haussen, D; Frankel, M; Nogueira, R
Abstract : Introduction: The smoking-thrombolysis paradox has been well described in myocardial infarction. However, its existence in the stroke population remains elusive. In the past decade, several studies have investigated the phenomenon with mixed results. We sought to determine whether clinical outcomes differ between smokers and non-smokers with acute ischemic stroke undergoing endovascular therapy. Methods: We reviewed our prospectively collected endovascular database at a tertiary care academic institution. All patients who underwent endovascular therapy for large vessel occlusion acute ischemic stroke were categorized into current smokers and non-smokers. Baseline characteristics, procedural radiological as well as outcome parameters where compared. Results: A total of 968 patients qualified for the study of which 189 (19.5%) were current smokers. Smokers were younger (60.78±11.95 vs. 66.41±15.05 years, p<0.001), had higher rates of dyslipidemia (49.7% vs 31.7%, p<0.001) and posterior circulation strokes (13.2% vs 7.8%, p=0.02, ) and lower rates of atrial fibrillation (21.1% vs 37.9%, p<0.001). There were no statistically significant differences between groups in terms of stroke severity (as assessed by NIHSS), baseline CT perfusion core and hypoperfusion volumes, CT angiogram collateral scores, as well as procedural variables. On univariate analysis, smokers had higher rates of good outcomes at 90 days (modified Rankin scale, mRS 0–2: 53.8% vs 42.8%, p=0.01) and similar rates of successful reperfusion (mTICI 2b-3) (92.1% vs 87.7%, p=0.09), parenchymal hematomas (4.2% vs 4%, p=0.84) and mortality at 90 days (20.2% vs 25.7%, p=0.14). Multivariate analysis showed that smoking was not independently associated with good outcomes. Stratifying for (1) stroke etiology and (2) anterior vs. posterior circulation topology yielded similar results. Conclusion: In stroke patients treated with mechanical thrombectomy, smoking does not seem to be associated with outcomes regardless of stroke subtype or location. Disclosures: J. Grossberg: None. M. Bouslama: None. L. Rebello: None. D. Haussen: None. M. Frankel: None. R. Nogueira: None.